2020
DOI: 10.3102/0162373720953128
|View full text |Cite
|
Sign up to set email alerts
|

Performance-Based Funding in American Higher Education: A Systematic Synthesis of the Intended and Unintended Consequences

Abstract: This systematic synthesis examines the intended and unintended consequences of performance-based funding (PBF) policies in higher education. Within this synthesis, we focus particularly on evidence from research studies with strong causal inference designs in an effort to understand the impacts of these policies. PBF adoption is generally associated with null or modest positive effects on the intended outcomes of retention and graduation, but there is also compelling evidence that PBF policies lead to unintend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
2
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 131 publications
(179 reference statements)
1
85
2
4
Order By: Relevance
“…Maslovaty and Kuzi (2002) argued that performance-based funding is antithetical, superficially espousing student achievement growth but primarily motivated in controlling the presentation of information and the associated tools through the threat of negative consequences. With the implementation of performance-based funding in 41 states, administrators are obligated to assess teachers' instruction, ensuring their methodology conforms to state standards, not necessarily student needs, ultimately expanding academic learning disparity in many in-need communities (Ortagus et al, 2020).…”
Section: Journal Of Educational Issuesmentioning
confidence: 99%
“…Maslovaty and Kuzi (2002) argued that performance-based funding is antithetical, superficially espousing student achievement growth but primarily motivated in controlling the presentation of information and the associated tools through the threat of negative consequences. With the implementation of performance-based funding in 41 states, administrators are obligated to assess teachers' instruction, ensuring their methodology conforms to state standards, not necessarily student needs, ultimately expanding academic learning disparity in many in-need communities (Ortagus et al, 2020).…”
Section: Journal Of Educational Issuesmentioning
confidence: 99%
“…Analyses of performance indicators and associated performance funding initiatives in Canada and the United States have found that they may, in some instances, not actually reliably assess the outputs they are intended or purported to measure. In some cases, performance funding fails to have the impact it was originally designed to have and can lead to unintended outcomes, such as restricting access for marginalized populations or further disadvantaging institutions which were underresourced to begin with [1], [13], [14]. For these reasons, the introduction of performance funding in Canada and elsewhere has been frequently regarded with some combination of skepticism, critique, and opposition.…”
Section: Performance Funding Debatesmentioning
confidence: 99%
“…Portanto, as universidades norte-americanas contam com o financiamento do governo federal, estadual e local. Apesar da participação desses recursos, as universidades americanas sempre foram norteadas a buscarem fontes de recursos adicionais (ORTAGUS et al, 2020). Esse país é composto por 50 estados e cada um deles possui sua própria maneira de financiar a educação superior (DOUGHERTY; REDDY, 2013).…”
Section: Afirma Queunclassified